2013
DOI: 10.1016/j.ydbio.2012.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Role of kruppel-like transcription factors in adipogenesis

Abstract: The zinc-finger transcription factors of the kruppel-like factor family (KLF) are critical in many physiological and pathological processes including cell proliferation, differentiation, inflammation, and apoptosis. Recently, there is increasing evidence that suggests these KLFs have an important role in fat biology. This review summarizes the role of KLFs in lipid metabolism, especially in adipogenesis, and reveals the relationship networks among members of KLF family in differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 114 publications
2
110
0
Order By: Relevance
“…For example, Zfp521 [30], Zfp423 [31], ZNF638 [32], ZNF395 [33], Snail [34] and kruppel-like transcription factors [35] were shown to be regulative in adipogenesis. In this group here, we detected eleven different ZFPs as well as Klf10, Klf9 and Klf5.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zfp521 [30], Zfp423 [31], ZNF638 [32], ZNF395 [33], Snail [34] and kruppel-like transcription factors [35] were shown to be regulative in adipogenesis. In this group here, we detected eleven different ZFPs as well as Klf10, Klf9 and Klf5.…”
Section: Resultsmentioning
confidence: 99%
“…KLFs constitute an interesting family of transcription factors involved in the regulation of diverse metabolic networks (Neve et al 2005;Lomberk et al 2013;Zhang et al 2013). Several KLF family members, including KLF2, KLF3, KLF4, KLF5, KLF6, KLF7, KLF9, and KLF15, have been implicated in different stages of adipogenesis (Wu and Wang 2013), but a role of KLF11 in adipogenesis has not been described. KLF11 has been shown to activate UCP1 expression in mouse bone marrow-derived stem cells (Yamamoto et al 2010); however, the impact of KLF11 on browning of adipocytes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first mammalian KLF, named KLF1/EKLF (erythroid Krüppel-like factor), was first identified as a master regulator of erythropoiesis [81], the KLF subfamily has reportedly been involved in various cellular processes, including cell proliferation, differentiation as well as apoptosis. Recently, a series of experiments demonstrated that many KLF members play vital roles in adipogenesis and adipose development (reviewed in [82, 83]) thus showing their potential therapeutic value in fighting against obesity. A total of 9 KLF members have been identified to be responsible for controlling white adipocyte development, of which KLF4, KLF5, KLF6, KLF8, KLF9, and KLF15 promote adipogenesis whereas KLF2, KLF3, and KLF7 inhibit adipogenesis.…”
Section: Zinc Finger Proteins In White Adipogenesismentioning
confidence: 99%